2014
DOI: 10.1016/s1569-9056(14)60421-8
|View full text |Cite
|
Sign up to set email alerts
|

427 A multicenter matched-pair analysis comparing robot-assisted versus open partial nephrectomy

Abstract: ObjectiveTo compare the perioperative, pathological and functional outcomes in two contemporary, large series of patients in different institutions and who underwent open partial nephrectomy (OPN) or robot-assisted PN (RAPN) for suspected renal tumours. Patients and MethodsThis was a retrospective, multicentre, international, matched-pair analysis comparing patients who underwent RAPN or OPN for suspected renal cell carcinoma.Data on patients who underwent OPN were extracted by an Italian observational registr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2014
2014
2015
2015

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 3 publications
(3 reference statements)
0
7
0
Order By: Relevance
“…In a recent matched-pair analysis comparing open and robot-assisted PNs from 23 centers, Ficarra et al found no significant difference in PSM rate among open (5.5%) and robot-assisted (5.7%) PNs (P ¼ .98). 16 Similarly, Springer and coworkers, showing results from a retrospective singleinstitutional study of 340 open and laparoscopic PNs for cT1 RCC, found comparable incidence of PSMs between the 2 groups (1.7% vs. 1.2%; P ¼ .09). 24 It appears still controversial whether the age at the time of surgery could be a predictor of PSMs.…”
Section: Riccardo Schiavina Et Almentioning
confidence: 81%
See 1 more Smart Citation
“…In a recent matched-pair analysis comparing open and robot-assisted PNs from 23 centers, Ficarra et al found no significant difference in PSM rate among open (5.5%) and robot-assisted (5.7%) PNs (P ¼ .98). 16 Similarly, Springer and coworkers, showing results from a retrospective singleinstitutional study of 340 open and laparoscopic PNs for cT1 RCC, found comparable incidence of PSMs between the 2 groups (1.7% vs. 1.2%; P ¼ .09). 24 It appears still controversial whether the age at the time of surgery could be a predictor of PSMs.…”
Section: Riccardo Schiavina Et Almentioning
confidence: 81%
“…SE), appear to be unrelated to margins status, according to the largest currently available evidence. 7,[14][15][16][17][18] We aimed to evaluate the predictors of PSM after NSS for RCC in one of the largest available prospective multi-institutional studies.…”
Section: Introductionmentioning
confidence: 99%
“…The advantages of MIPN include less blood loss, shorter hospital stay, improved cosmesis, less postoperative pain, and fewer postoperative complications than open PN while maintaining early oncologic and functional outcomes. 19,20 However, the ability to manage intra-abdominal visceral and perinephric adipose tissue in obese patients during MIPN can pose a significant challenge for exposure, hilar dissection, tumor resection, and renorrhaphy.…”
Section: Discussionmentioning
confidence: 99%
“…89 Surgeons at high-volume PN centers are attempting maximal renal preservation with early vascular unclamping, or even zero-ischemia, though these patients are highly selected and the approach may not be applicable to the elderly population. 90 Other nephron-sparing options include cryoablation, radiofrequency and thermal ablation, providing important alternatives for patients ineligible for surgery.…”
Section: Renal Cell Carcinomamentioning
confidence: 99%